The Pleurothallidinae: extremely high speciation driven by pollination adaptation - Karremans Lok, Adam Philip (2019)
The generic and subgeneric classification of Pleurothallidinae has traditionally been a hazardous task. The main challenge has been understanding the underlying relationships of the immensely diverse, +5100 accepted species in the subtribe. Species groups that could be easily separated from others by means of specific floral traits have been shown to be non—monophyletic using molecular techniques. Morphological characters related to pollination that have frequently been used to group species, such as anther position and pollinia morphology, have evolved independently in most of the major clades of Pleurothallidinae. Adaptation to specific pollinators is likely to be one of the main drivers for morphological similarity in the reproductive organs of unrelated species. Myophily, or pollination by flies, may be common to members of the subtribe; however, the pollinators of most species and species groups are still unknown. We have compiled a dataset of pleurothallid pollinators by combining pollination reports from the literature and additional unpublished observations and have plotted the occurrence of diverse Diptera families across the Pleurothallidinae phylogeny. As far as we can tell, floral visitors have been documented for only about one fourth of the genera (i.e., Acianthera, Andinia, Dracula, Lepanthes, Echinosepala, Masdevallia, Octomeria, Phloeophila, Pleurothallis, Porroglossum, Specklinia, Stelis, Trichosalpinx, and Teagueia), and just about 2% of all known species belonging to the subtribe. Many of these reports are made for the first time, and most are based on few observations. The number species and genera of Pleurothallidinae for which pollination data are available is far from being enough to allow for an accurate estimation of all the different orchid-insect interactions. A robust DNAvbased phylogeny of the subtribe, however, allows adequate placement of known relationships. Diverse pollination systems employing flies of the families Anthomyiidae, Calliphoridae, Cecidomyiidae, Ceratopogonidae, Chloropidae, Drosophilidae, Keroplatidae, Mycetophilidae, Otitidae, Phoridae, Richardidae, Sarcophagidae, Sciaridae, Tephritidae, and Ulidiidae are found in the subtribe. Most of them are shown to have evolved several times independently, and adaptation to one family or another occurs even among closely related species. Finally, based on the young age of the subtribe in contrast to that of these Diptera families, pollination systems in the Pleurothallidinae are most likely due to the orchid adapting to a preexisting insect/behavior rather than a case of coevolution.